2009
DOI: 10.1007/s10461-009-9562-x
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Methods Evaluation of the Effect of the Protect and Respect Intervention on the Condom Use and Disclosure Practices of Women Living with HIV/AIDS

Abstract: This mixed methods study evaluated the efficacy of an intervention to increase HIV status disclosure and condom use among 184 women living with HIV/AIDS (WLH/A). Participants were recruited from an HIV clinic and randomly assigned to: (1) a comparison group, who received brief messages from their health care providers (HCPs), or; (2) an intervention group, who received messages from HCPs, a group-level intervention, and peer-led support groups. Participants completed risk surveys at baseline, 6-, 12-, and 18-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
67
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 26 publications
0
67
0
Order By: Relevance
“…Even after contact with authors by e-mail, another 3 studies that met the inclusion criteria could not be included in the meta-analysis, since no further information was obtained about either the absolute number of women living with HIV engaged in safe sex or the mean and standard deviation of protected sexual acts 42,43,44 , besides another study due to lack of further information on analyses done on intervention effects by gender 45 . We identified only 1 non-randomized study 46 which provided complete data on female participants, which was not included in the meta-analysis to avoid potential confounding.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Even after contact with authors by e-mail, another 3 studies that met the inclusion criteria could not be included in the meta-analysis, since no further information was obtained about either the absolute number of women living with HIV engaged in safe sex or the mean and standard deviation of protected sexual acts 42,43,44 , besides another study due to lack of further information on analyses done on intervention effects by gender 45 . We identified only 1 non-randomized study 46 which provided complete data on female participants, which was not included in the meta-analysis to avoid potential confounding.…”
Section: Resultsmentioning
confidence: 99%
“…We decided to include the 5 interventions in the systematic review and describe the results reported narratively by the authors. All 5 studies were developed in the United States, and 3 involved interventions targeting women living with HIV 42,43,44 . Kalichman et al 45 conducted interventions for women and men living with HIV separately, and Fisher et al 46 included both female and male participants in the intervention or comparison groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations